Silk-Aloe Vera Composite Piezoelectric Film: A New Paradigm in Eco- Friendly Piezoelectrics - Bhagavathi, K. Aditya; Bonam, Satish; Joseph, Jose; Rao, Karri Trinadha; Singh, Shiv Govind; Vanjari, Siva Rama Krishna (IEEE journal on flexible electronics, 2024)
Piezoelectric materials derived from biological sources are given greater consideration in the present era due to their advantages, such as biocompatibility, sustainability, and potential for tailoring properties through chemical modification and genetic engineering. Silk, a bio-piezopolymer, derived from the silk glands of various species of silkworms, is extensively studied for its piezoelectric properties and applications thereof. This article presents the development of a composite bio-piezopolymer, amalgamating the material properties of silk and the extracts taken from a tropical desert plant, aloe vera. A comprehensive material characterization protocol is embraced to assess the performance of the thin film formed from the silk-aloe vera (SAV) composite solution. In addition to an improvement in the piezoelectric characteristics, the composite film exhibited excellent surface uniformity and crystallinity, proving its potential for real-time applications. Pressure sensors were fabricated with SAV composite films and characterized using a custom-built test setup. The characterization results surpassed the performance achieved by pressure sensors fabricated using only silk thin film.